Thermostable lamprey variable lymphocyte receptor antibody for detection of Plasmodium falciparum histidine rich protein-2 - Deepak Tomar; Balwan Singh; Masayuki Hirano; Samadhi Senanayake; Michael Aidoo; Eric Rogier; Oskar Laur; Brantley R. Herrin; Venkatachalam Udhayakumar (Scientific Reports)
Abstract Lampreys use variable lymphocyte receptors (VLR) comprising leucine-rich-repeat (LRR) segments for antigen recognition, distinct from immunoglobulin-based receptors of jawed vertebrates. Lamprey VLRs are as diverse and antigen-specific as immunoglobulin-based antibodies, with unique advantages including high avidity, pH stability, and recognition of novel antigen epitopes. Here we describe the generation of VLR monoclonal antibody against histidine rich protein-2 (HRP-2) of Plasmodium falciparum, a causative agent of malaria. HRP-2, expressed by all parasite stages and secreted into plasma, serves as an effective biomarker of infection. Lamprey larvae immunized with purified HRP-2 protein produced specific VLRB antibodies with relatively high serum titers. Using white blood cells from immunized lampreys, we constructed VLR cDNA libraries expressed on yeast surface. Through yeast display screening, we selected recombinant VLRB antibody 5A10 with high affinity and specificity for HRP-2, recognizing both recombinant and native proteins from P. falciparum culture supernatants and infected patient samples. The antibody retains its binding capacity at temperatures up to 70 °C, significantly outperforming a commercial mouse IgG-based anti-HRP-2 antibody. This HRP-2-specific VLR antibody shows promise for improved malaria diagnostics, particularly in tropical regions requiring heat-stable tests.